(untitled) (International Journal of Communication Systems and Network Technologies, 2021)
This Paper presents the Internet is considering as an important information repository now. Without it no single work is possible. It is even regarded as one of the de facto techniques that are used in transmission. In the enterprise world, including all the forms of communication particularly the Email is most common form. But all people can not use the internet. Because you need to know what’s on the screen to access the internet. It doesn’t matter if you don’t see it. Thatleads to making the internet as not useful technology for blind and uneducated people. The currently available structure, such as TTS and ASR screen readers, do not allow visually impaired people to use the Internet efficiently enough. With around 285 million people with visual impairments worldwide, they need access to the Internet to communicate.